THE EFFICACY OF SEVERAL DISINFECTANTS ON ALGINATEMATERIAL: THE EXPERIMENTAL STUDY - Dr. Muhammad Aamir Rafique; Dr. Aimon Salam; Dr. Ambreen Usmani; Dr. Sameen Baleegh Ur Rehman; Dr. Ghulam Ishaq; Dr. Azam Shahzad (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Dental impressions, particularly alginate (irreversible hydrocolloid), are easily contaminated with saliva and blood, making them potential vectors for cross-infection. Although disinfection is recommended, inconsistent protocols and concerns about dimensional stability limit routine practice. This study compared the efficacy of 1% chlorhexidine, 0.5% sodium hypochlorite and tap water on microbial reduction in alginate impressions. Methods: Maxillary arch impressions were taken using standard alginate technique. Each impression’s palatal surface was divided into four sections: Group 1: Control (no disinfection) Group 2: Tap water rinse Group 3: 0.5% sodium hypochlorite Group 4: 1% chlorhexidine Each section received its assigned treatment for 10 minutes in sterile bags. Microbial swabs were inoculated on blood agar and incubated at 37 °C for 24 hours. Colony-forming units (CFUs) were counted and analyzed using one-way ANOVA with post-hoc comparisons. Results: Mean CFU counts (×10⁶) were 63.6 ± 5.4 (control), 19.9 ± 3.1 (tap water), 2.2 ± 0.7 (sodium hypochlorite) and 1.2 ± 0.4 (chlorhexidine). ANOVA revealed significant differences among groups (p < 0.001). Both disinfectants produced >96% reduction in microbial load compared with control (p < 0.001), whereas tap water produced only a modest but significant reduction (≈69%, p = 0.032). No significant difference was observed between chlorhexidine and sodium hypochlorite. Conclusion: 1% chlorhexidine was the most effective disinfectant for alginate impressions, closely followed by 0.5% sodium hypochlorite. Incorporating chlorhexidine into routine disinfection can improve infection control without compromising impression material.